30. EPIDEMIOLOGICAL, CLINICAL FEATURES AND OUTCOMES IN PATIENTS WITH HIV/AIDS ADMITTED TO HOSPITAL FOR TROPICAL DISEASE (Vietnam Journal of Community Medicine, 2024)
Background: Human Immunodeficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) continue to be a major global health. Highly-active antiretroviral therapy (HAART) had a dramatic impact on the AIDS epidemic; in particular, it has greatly changed the mortality profile for human immunodeficiency virus (HIV)-infected individuals. As survival increases, so does the likelihood that diseases other than those related to AIDS will incur among HIV-infected individuals.Objectives: To describe epidemiological, clinical features and outcomes in patients with HIV/ AIDS at the Hospital for Tropical Disease in Ho Chi Minh City.Methods: Describe a retrospective case series in all patients with HIV/AIDS admitted to Department E, Hospital for Tropical Disease from January 2021 to May 2021.Results: 203 patients with HIV/AIDS were enrolled in the study. The male/female ratio was 5/1; most patients (56,2%) were aged 31-50, 46,3% patients were malnutrition. 62,3% patients were diagnosed with < 6 months, 74,4% had T CD4+ < 200 cells/mm3. 11,8% patients died. Fever is the most common symtom (57,1%). Diseases did not related to AIDS stage include infections (36,9%), oral candidiasis (19,2%), pulmonary tuberculosis (17,3%). HIV-related opportunistic infections include pneumocystis jirovecii pneumonia (43,2%), extrapulmonary tuberculosis (24%).Conclusion: The rate of hospitalization due to opportunistic diseases related to HIV/AIDS is still high. Increase hopitalization rates due to illnesses unrelated to HIV/AIDS.
Keywords: HIV, AIDS, ARV, HIV-related opportunistic infections